Higlighting the Gender Perspective of Family Planning in Malang City - Arfida Boedirochminarni; Zainal Arifin (Universitas Muhammadiyah Malang, 2020)
The Gender perspective of family planning participants in Malang, especially in the KB village, Bareng, because according to the Women's Empowerment, Child Protection, Population and Family Planning (DP3AP2KB) Office, is located at Jl. Ki Ageng Gribig No.5 Malang Postal Code 65173. Having a vision that is